2017 IEEE 2nd Advanced Information Technology, Electronic and Automation Control Conference (IAEAC) 2017
DOI: 10.1109/iaeac.2017.8054335
|View full text |Cite
|
Sign up to set email alerts
|

Carrier phase estimation in dispersion-unmanaged optical transmission systems

Abstract: Abstract-The study on carrier phase estimation (CPE) approaches, involving a one-tap normalized least-mean-square (NLMS) algorithm, a block-wise average algorithm, and a Viterbi-Viterbi algorithm has been carried out in the long-haul high-capacity dispersion-unmanaged coherent optical systems. The close-form expressions and analytical predictions for biterror-rate behaviors in these CPE methods have been analyzed by considering both the laser phase noise and the equalization enhanced phase noise. It is found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 55 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…It has been demonstrated that the one-tap normalized LMS carrier phase estimation behaves similar to the differential phase estimation [28,53,55,76], of which the BER floor in the m-PSK coherent optical transmission systems can be approximately described by the following analytical expression, (15) where σ is the square root of the phase noise variance. The schematic of the onetap normalized LMS carrier phase estimation is illustrated in Figure 6.…”
Section: The Normalized Lms Carrier Phase Estimationmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been demonstrated that the one-tap normalized LMS carrier phase estimation behaves similar to the differential phase estimation [28,53,55,76], of which the BER floor in the m-PSK coherent optical transmission systems can be approximately described by the following analytical expression, (15) where σ is the square root of the phase noise variance. The schematic of the onetap normalized LMS carrier phase estimation is illustrated in Figure 6.…”
Section: The Normalized Lms Carrier Phase Estimationmentioning
confidence: 99%
“…The performance of the block-wise average carrier phase estimation method in the m-PSK coherent optical communication system can be derived based on the Taylor expansion of the estimated carrier phase error, and the BER floor in the block-wise average carrier phase estimation can be described using the following expression [52,53,55,79]:…”
Section: The Block-wise Average Carrier Phase Estimationmentioning
confidence: 99%
See 3 more Smart Citations